Comparison of United States and Italian experiences with sudden cardiac deaths in young competitive athletes: Are the athletic populations comparable? - Maron, B. J.; Haas, T. S.; Doerer, J. J.; Thompson, P. D.; Hodges, J. S. (The American Journal of Cardiology, 2009)
Controversy has evolved over the most practical and effective strategy for preparticipation cardiovascular screening of competitive athletes to detect unsuspected cardiovascular disease and prevent sudden death on the athletic field. Athlete screening in the Veneto region of Italy is part of a national program (with 12-lead electrocardiography) that has reported the detection of previously undiagnosed hypertrophic cardiomyopathy and a decrease in the cardiovascular death rate in young athletes. In this study, over time periods of similar length, cardiovascular-related mortality rates in Veneto athletes were compared with those of a demographically similar region of the United States (Minnesota) in which screening is limited to history and physical examination. There were 55 sudden cardiovascular deaths reported in Veneto over 26 years (2.1/year), compared with 22 deaths in 23 years (0.96/year) in Minnesota. Over the recent and comparable 11-year period, 1993 to 2004, 12 deaths were reported in Veneto and 11 in Minnesota. When analyzed as deaths per 100,000 person-years, Veneto exceeded Minnesota for all years combined (1.87 for 1979 to 2004 vs 1.06 for 1985 to 2007, respectively, p = 0.006), although the 2 regions did not differ significantly for 1993 to 2004 (0.87 vs 0.93, respectively, p = 0.88) or most recently for 2001 to 2004 (0.43 vs 0.90, respectively, p = 0.38). In conclusion, sudden cardiovascular deaths in young competitive athletes occurred at a low rate in both Veneto and Minnesota. Despite different preparticipation screening strategies, athlete sudden death rates in these demographically similar regions of the United States and Italy have not differed significantly in recent years. These data do not support a lower mortality rate associated with preparticipation screening programs involving routine electrocardiography and examinations by specially trained personnel.